Women with TT genotype for eNOS gene are more responsive in lowering blood pressure in response to exercise - Sponton, Carlos H. G.; Rezende, Tiago M.; Mallagrino, Pamella A.; Franco-Penteado, Carla F.; Bezerra, Marcos Andre C.; Zanesco, Angelina [UNESP] (Lippincott Williams & Wilkins, 2010)
Introduction The aim of this study was to investigate whether -786T > C endothelial nitric oxide synthase (eNOS) gene polymorphism might influence the effect of long-term exercise training (ET) on the blood pressure and its relationship with NO production in healthy postmenopausal women. Design Longitudinal study.Method Fifty-five postmenopausal women were studied in a double-blinded design. ET was performed for 3 days a week, each session consisting of 60 min during 6 months, in an intensity of 50-70% VO(2max). After that, eNOS genotype analysis was performed and women were divided into two groups: TC + CC (n = 41) and TT (n = 14) genotype.Results No changes were found in the anthropometric parameters after ET in both the groups. Systolic and diastolic BP values were significantly reduced in both the groups, but women with TT genotype were more responsive in lowering BP as compared with those with TC + CC genotype. Plasma nitrite/nitrate concentrations were similar at baseline in both the groups, but the magnitude of increment in NO production in response to ET was higher in women with TT genotype as compared with those with TC + CC genotype.Conclusion Our study shows clearly that women with or without eNOS gene polymorphism had no differences in NO production at basal conditions, but when physical exercise is applied an evident difference is detected showing that the presence of -786T > C eNOS gene polymorphism had a significant impact in the health-promoting effect of aerobic physical training on the blood pressure in postmenopausal women. Eur J Cardiovasc Prev Rehabil 17:676-681 (C) 2010 The European Society of Cardiology
Keywords: blood pressure; eNOS gene polymorphism; physical exercise; women